Levantamento etnobotânico participativo entre os moradores do Quilombo da Fazenda - Núcleo Picinguaba, Ubatuba, SP, Brasil: diálogos entre os conhecimentos tradicionais e acadêmicos - Yazbek, Priscila Baptistella [UNIFESP] (2018)
This dissertation focuses on the survey of possible bioactive compounds, as well as the conceptions of diseases and treatments that involve medicinal plants’ use based on indications of use by residents of Quilombo da Fazenda, located in Serra do Mar State Park – Nucleus Picinguaba, Ubatuba, Brazil. The activities were carried out jointly by researchers and community residents, entitled local collaborators, allowing analysis of connections and disconnections between academic and traditional scientific knowledge, contributing to the strengthening of local knowledge and listing bioactive potentials according to the context in which they are inserted. The project counted with trainings that were offered to collaborators about collection of plants and ethnobotanical data. Together with technical team, and using ethnobotany methods and techniques, the collaborators selected and interviewed residents indicated as the greatest connoisseurs of plants’ use. Data about uses of each species were recorded on sheets specially prepared for this project and the respective plant was collected and deposited at the Herbarium Municipal-SP (PMSP). Interviews generated 279 therapeutic indications of 112 plants with possible bioactive compounds. These indications were grouped into 14 ethical categories of use, allowing the deepening of themes according to the most indicated categories, parts of use, forms of preparation, administration and the use of species with other components. The botanical identifications allowed analysis of the species and families most present on treatments and species distribution. Quilombola knowledge, relations between quilombolas and plants, vegetal species forms of identification and classification, observed through ethnography, were recorded in a field diary and later systematized, analyzed and discussed. In addition, in order to have some of this knowledge documented for current residents and future generations, as they wish, such data were used in a book and a documentary production. This study development promoted participation of community residents, strengthening quilombolas’ knowledge and ways of knowing, and it has demonstrated that contributions of traditional knowledge to academic science go far beyond the usefulness of plants.